Delio, Fadhil. “Western Sociology and its Theoretical Dualism,” Year 3, Issue 11 (Winter 1418 AH/ 1998 CE), Pp. 81-117. - دليو فضيل (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 1998)
Fadhil Delio explains the origins of the social sciences in Western epistemological and methodological frameworks, and addresses Western sociology and its duality, defined in: objectivity and subjectivity; social structure and social action; collective and individual; universal and particular; and concordance and conflict. He presents an overview of the problem dimensions and attempts to synthesize the elements of the duality, discovering that these dualities are in reality only a reflection of the diversity of dimensions that constitute social reality. His study demonstrates the inability of Western philosophical frames of reference to comprehend the statements, scientific frameworks, and appropriate methodologies to accommodate and deal with duality, concluding with illustrative forms and tables on the Western point of reference and the Western dualities based on theoretical prefaces.